Comparative analysis of calculation methods for Cable Curve of Landscape Suspension Bridges. Issue 4 (October 2020) - Jiang, Tianhua; Yu, Yalu; Zhang, Xiucheng; Huang, Wen
Abstract: The main cable curve control of landscape suspension bridge is not only the premise of achieving the ideal completed state, but also the key problem of suspension bridge construction control. By analysing the characteristics of the main cable of anchored double tower landscape suspension bridge, the analytical equations for calculating the main cable curve of suspension bridge are derived by parabolic method and segmented catenary method. Then combined with practical work, the main cable curve was calculation methods by using the two calculation methods. Results show that both the parabolic method and the catenary method can be used for the preliminary design of the main cable curve of the landscape suspension bridge, but the segmented catenary method with repeated revision iteration has higher accuracy.